High‐Performance Electrocatalytic Conversion of N2 to NH3 Using Oxygen‐Vacancy‐Rich TiO2 In Situ Grown on Ti3C2Tx MXene. Issue 16 (28th February 2019) - Fang, Yanfeng; Liu, Zaichun; Han, Jingrui; Jin, Zhaoyong; Han, Yaqian; Wang, Faxing; Niu, Yusheng; Wu, Yuping; Xu, Yuanhong
Abstract: To achieve the energy‐effective ammonia (NH3 ) production via the ambient‐condition electrochemical N2 reduction reaction (NRR), it is vital to ingeniously design an efficient electrocatalyst assembling the features of abundant surface deficiency, good dispersibility, high conductivity, and large surface specific area (SSA) via a simple way. Inspired by the fact that the MXene contains thermodynamically metastable marginal transition metal atoms, the oxygen‐vacancy‐rich TiO2 nanoparticles (NPs) in situ grown on the Ti3 C2 T x nanosheets (TiO2 /Ti3 C2 T x ) are prepared via a one‐step ethanol‐thermal treatment of the Ti3 C2 T x MXene. The oxygen vacancies act as the main active sites for the NH3 synthesis. The highly conductive interior untreated Ti3 C2 T x nanosheets could not only facilitate the electron transport but also avoid the self‐aggregation of the TiO2 NPs. Meanwhile, the TiO2 NPs generation could enhance the SSA of the Ti3 C2 T x in return. Accordingly, the as‐prepared electrocatalyst exhibits an NH3 yield of 32.17 µg h −1 mg −1 cat. at −0.55 V versus reversible hydrogen electrode (RHE) and a remarkable Faradaic efficiency of 16.07% at −0.45 V versus RHE in 0.1m HCl, placing it as one of the most promising NRR electrocatalysts. Moreover, the density functional theory calculations confirm the lowest NRR energy barrier (0.40 eV) of TiO2 (101)/Ti3 C2 T x compared with Ti3 C2 T x or TiO2 (101) alone. Abstract : Oxygen‐vacancy‐rich TiO2 nanoparticles in situ grown on the MXene nanosheets (TiO2 /Ti3 C2 T x ) are achieved via a one‐step ethanol‐thermal treatment of Ti3 C2 T x MXene. Based on the synergistic effects of Ti3 C2 T x and TiO2, TiO2 /Ti3 C2 T x exhibits much higher N2 reduction reaction (NRR) performance than that of the Ti3 C2 T x or TiO2 alone. Density functional theory calculation is applied to confirm the NRR mechanism.